The effects of metformin in type 1 diabetes mellitus - Selvihan Beysel; Ilknur Ozturk Unsal; Muhammed Kizilgul; Mustafa Caliskan; Bekir Ucan; Erman Cakal (BMC Endocrine Disorders, 2018)
Abstract Background This retrospective study investigated the effect of adding metformin to pharmacologic insulin dosing in type 1 diabetics on insulin therapy 1 year after treatment compared with patients on insulin therapy alone. Methods Twenty-nine adults with type 1 diabetes who had metformin added to their insulin therapy for 12 months were compared with 29 adults with type 1 diabetes who remained on insulin-alone therapy. Results Fifty-eight patients with C peptide negative-type 1 diabetics (26 females, mean age: 29.01 ± 7.03 years, BMI: 24.18 ± 3.16 kg/m2) were analyzed. Age, sex, body weight, insulin dose requirement, plasma glucose (PG), blood pressure (BP), and lipids did not differ between groups before treatment (p > 0.05). Metabolic syndrome (44.8 vs 41.4%, p > 0.05) did not differ between the metformin-insulin and insulin alone groups before treatment. Metabolic syndrome was more decreased in the metformin-insulin group than in the insulin alone group after treatment (−8.9 ± 1.3 vs. 2.5 ± 0.6%, p = 0.028). Insulin dose requirement was lower in the metformin-insulin group than in the insulin alone group (−0.03 vs. 0.11 IU/kg/d, p = 0.006). Fasting PG (−26.9 ± 54.2 vs. 0.7 ± 29.5 mg/dL, p = 0.022) and postprandial PG (−43.1 ± 61.8 mg/dL vs. −3.1 ± 40.1 mg/dL, p = 0.010) was more decreased in the metformin-insulin group than in the insulin alone group. Body weight, lipids, and HbA1c did not differ between the groups (p > 0.05). Conclusions Metformin decreased glucose concentrations, reduced metabolic syndrome, as well as insulin dose requirement more than insulin therapy alone, 1 year after treatment. These results were independent of blood lipid improvement or weight loss, although on average weight remained decreased with metformin-insulin therapy, whereas the average weight increased with insulin therapy alone.